Artificial tears containing hyaluronic acid in dry eye syndrome treatment - I. A. Pronkin; D. Yu. Maichuk (Российский офтальмологический журнал, 2018)
Today, artificial tears containing hyaluronic acid are the first choice remedy in dry eye syndrome treatment. This is due to unique properties of hyaluronan, such as mucoadhesion, high hydrophilia, adaptive viscoelasticity depending on pH level, composition similar to the native tear, an ability to stimulate migration and proliferation of epitheliocytes, to affect cell diffusion, to have a protective and antioxidative effect on the cells, etc. However, while choosing artificial tear drops we have to take account not only of the presence of hyaluronan as the main ingredient, but also ofthe qualitative characteristics of its molecules, type and concentration of the buffer, presence of a preservative agent, and other factors that can weaken hyaluronan beneficial features, cause an allergy, worsen the viscoelastic properties of the solution, etc. // Russian Ophthalmological Journal, 2016; 4: 94-104. doi: 10.21516/2072-0076-2016-9-4-94-104.